STABILISASI TANAH RAWA MENGGUNAKAN LIMBAH GERGAJI KAYU DAN SERBUK LIMBAH BOTOL KACA TERHADAP PENINGKATAN NILAI CBR - Irma Wirantina Kustantrika (FORUM MEKANIKA, 2017)
Marshland is a soft soil containing clays, silt and peat. The clay / silt is a type of plastic cohesive which hasadhesive properties between the grains and able to be permanently formed continuously with relativelymoderate pressure without breakage. However, clay or silt becomes inconsistent with loading, resulting in alarge decrease (instability). Marshland has an unstable behavior requires an effort to fix it. One of the effortsto repair the marshland chemically can be done by reusing waste wood and glass bottle waste as stabilizationmaterial. Waste wood is burnt to ash and the waste of glass bottles is recycled by being crushed to becomepowder. Waste wood and waste powder of glass bottles serve as fillers and binders on marshland.Based on the test result, the optimum percentage value of wood waste ash addition and powder of glass bottlewaste in marshland with mixture of 10% wood waste ash and 10% powder of glass bottle waste with 7 days ofcuring with CBR value of 4.5325%. This indicates that the land with the CBR value (CBR 3% - 7%) can beused as a subgrade layer for residential roads or local roads with low traffic